Elementary School Heads’ Profile, Level of Competence, and Experiences in Crisis Management - Domingo, Flordeliza C.; Antonio, Vida V. (Future Science / FSH-PH Publications, 2025)
Crisis management is a vital competency for elementary school heads amid increasing emergencies that disrupt education. This study assessed the profile, competence, and experiences of 150 public elementary school heads in Ilocos Norte, Laoag City, and Batac City, Philippines, using a descriptive research design using validated questionnaire and interviews. Results showed that most respondents were female, aged 41–60, with master’s units or degrees and more than ten years of service. They demonstrated a proficient level of competence in the four phases of crisis management: mitigation and prevention, preparedness, response, and recovery, with notable strengths in preparing drills, communication, and recovery routines, but gaps in mitigation strategies, crisis communication, suicide prevention, and psychosocial support. Qualitative findings revealed recurring challenges, including limited funding, insufficient crisis-specific training, and weak coordination with external agencies. These results suggest that while school heads are generally competent, their capacities are not yet fully developed to meet the demands of complex crises. The study recommends the establishment of a Comprehensive Crisis Management Program (CCMP) that emphasizes proactive planning, effective communication protocols, psychosocial support systems, and collaboration with local government units to enhance school resilience and ensure the safety and well-being of learners and staff.